Case Report: Surgical management of primary lymphedema with a novel PROX1 mutation involving upper and lower limbs - Chen, Junzhe; Wang, Liangliang; Wu, Xiangkui; Wu, Bihua; Li, Hai; Xiao, Shune; Deng, Chengliang (Frontiers in Genetics, 2025)
BackgroundPrimary lymphedema (PL) is a chronic condition characterized by abnormal swelling of tissues due to impaired lymphatic drainage, leading to increased deposition of adipose tissue and fibrosis. Although several pathogenic variants in genes associated with PL have been identified, a significant number of cases remain unexplained, suggesting the possibility of undiscovered genetic links.Case presentationThis report describes a novel heterozygous mutation in the PROX1 gene (c.1019C>G, p.S340C) identified in a 59-year-old male patient with PL affecting both upper and lower extremities, indicating its potential role in lymphatic dysfunction. A comprehensive treatment strategy—combining conservative decongestive therapy for the less severely affected upper limb with radical reduction while preserving perforators (RRPP) and vascularized lymph node transfer (VLNT) for the severely affected lower limb—resulted in significant improvements in limb circumference, lymphatic transport, and overall quality of life.ConclusionThis report highlights the efficacy of combining RRPP and SC-VLNT in treating advanced-stage PL and emphasizes the importance of considering genetic factors in the management of this complex disease.